Rampenstufen und Schuttrampen als Abtragungsformen in ariden Schichtstufenlandschaften - Blume, Helmut; Barth, Hans Karl (ERDKUNDE, 1972)
Flat-irons and talus-flat-irons are characteristic landforms of erosion in arid climates. They owe their origin to the combined efficiency of sheet floods and linear erosion after heavy rainfalls when a sudden increase in drainage occurs. As flat-Irons are limited in their occurrence to hog backs it is clear that their morphological appearance is bound up with specific tectonic presuppositions. It can be further established that their occurrence is also bound up with certain petrographic conditions. An important precondition for the secondary cuestas on dip slopes is a series of resistant strata seperated by thin, less resistant layers. On the other hand the front slope of a hogback only presents the character of a flat-iron if the resistant scarp former is underlain by less resistant layers of a greater thickness especially in the lower parts of the front slope. Talus-flat-Irons are also bound up with certain tectonic and petrographic presuppositions. A level rock stratification is the first precondition, the second is the position of a resistant cuesta-forming stratum resting on a very thick but morphologically non-resistant stratum in the lower part of the front slope. In addition it appears that talus-flat-irons only will be formed where a relatively thin amount of debris can be found. Thus talus-flat-irons, which are only limited to a few scarplands in arid regions are also limited in their distribution to the front slopes of cuesta hill spurs (outliers'* viz. BLUME 1971, p. 14). Flat-irons and talus-flat-irons are thus special features of landform development in arid scarplands. Their morphology and distribution results from climatic, tectonic, and petrographic conditions.